EMPIRIC JURIDICAL REVIEW OF THE WEAK LEGAL PROTECTION OF INDONESIAN MIGRANT WORKERS - Alfalachu Indiantoro; endrawati Aprilia; Septyana Wulandari; Dita Ajeng Yulianie (Universitas Muhammadiyah Ponorogo, 2020)
The narrowness of land for employment, low education, economic pressure requires that most Indonesians must try their fortune abroad in order to meet their daily needs. Reflections on Indonesia's life are currently experiencing a decline in quality, because Indonesia can be said to be the largest export of migrant workers to several countries such as Taiwan, Hong Kong, Singapore, Malaysia, Korea. With this phenomenon the government is seen as failing to prosper the lives of its people.